Creation and manipulation of quantum states of light and cold atoms using Rydberg states - Laycock, Thomas Henry (2013)
Rydberg atoms are often proposed as the basis of quantum computing and quantum information protocols. One of the central reasons for this is that they provide a strong and long-ranged interaction that can be coherently switched on and off. This thesis details two techniques which use the exaggerated properties of Rydberg atoms to manipulate both the quantum state of the atom itself and that of the external light field.